Evaluasi Pembelajaran Menurut Hadis - Ridwan, Addini Husna; Nasution, Rizka Fadhilah; Arienza, Taffana Idzni (STIKes Ibnu Sina Ajibarang, 2025)
Learning evaluation is an essential component of the Islamic education system as it serves to assess the achievement of learning objectives and measure students’ development. This study aims to examine the concept of learning evaluation according to the Hadith of the Prophet Muhammad Shallallahu ‘Alaihi Wasallam and its relevance in modern educational contexts. The research employs a qualitative descriptive approach with a literature study method, using sources from hadith collections, Islamic education books, and scientific journals. The findings reveal that the Prophet’s hadith provides a strong foundation for the implementation of learning evaluation based on three main domains: cognitive, affective, and psychomotor. Furthermore, the hadith emphasizes sincerity, justice, and exemplary behavior as essential principles in the evaluation process. The implementation of these values in modern education requires teachers to assess not only academic performance but also students’ moral and spiritual aspects. Thus, learning evaluation based on hadith serves as guidance for achieving a balanced education between knowledge, morality, and skills.